'Threads of Identity': Uncovering the benefits and tensions found in the hand-sewn signature as a method of engagement to challenge stereotypes about embroidering with boys. (1st December 2020) - Setterington, Lynn
This article describes a stitch-based research project that took place in 2016 in Manchester. It involved the Ahmed Iqbal Ullah Race Relations Archive, Burnage Academy for Boys and a professional embroiderer. Central to the enquiry is a signature cloth ‐ a textile made up of hand-sewn autographs ‐ used as a vehicle to explore young male identity and stereotypes about embroidery. The investigation signposts the flexibility of the signature that is utilized in the research to locate accessible activities and processes. In so doing, it formulates new avenues to access historical textile artefacts and illuminates their significance and contemporary relevance. The enquiry also outlines some of the tensions and dilemmas that permeate socially engaged practice(s) and offers new insights into the stitch-based collaborative/participatory process, in which the production of the tactile artefact is but one element; for alongside the stitch workshops a commemorative banner was a second outcome, made to memorialize a pupil killed in the school in a racially motivated crime in 1986. Shedding light on embroidery as a form of social engagement, the investigation also provides evidence of its applicability as an alternative, tactile means of communication. It similarly reveals and elucidates the dynamics inherent in this stitch-based community collaboration and draws attention to some of the planned and unexpected outcomes that emerge. The methodology offers a transparent model for those who may engage in similar practices and highlights its applicability to different audiences.